THE EFFECTIVENESS OF TEACHING POETRY WRITING USING KINETIC SHORT FILMS BY PUTRI TANJUNG IN GRADE X AT SMK PUI GEGESIK FOR THE ACADEMIC YEAR 2023/2024 - Nurindah, Siti; Efendi, Irfan; Fajri, Khoirul (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
This study aims to determine the effectiveness of learning to write poetry using short film media Kinetik by Putri Tanjung in class X SMK PUI Gegesik. This type of research is Experimental Research using Quasi experimental design. The population in this study was class X SMK PUI Gegesik. The sample in this study were students of class X DKV 1 as an experimental class consisting of 32 students and class X DKV 3 as a control class consisting of 32 students. Data collected by written test technique, namely pre-test and post-test. It was shown that media of kinetic short film is used effectively in learning to write free poetry because of the significant difference between the control class and the experimental class; namely, learners who used Kinetic short film media with those who did not use it. It can be seen based on the t-test results of the Pre-test and post-test scores in the control class and experimental class conducted with the help of the SPSS program. The result of statistical calculation using t test of two independent samples (independent sample t test). The obtained statistic is 4.075, with t table: 1.670. Thus, t statistic > t table (4.075 > 1.670).